Research on music therapy from 2013 to 2022: a bibliometric and visualized study - Zhi, Liang; Hou, Dianrui; Hong, Yaqing; Ke, Meihua; Zhang, Qingfang; Wang, Yulong; Long, Jianjun (Frontiers in Psychiatry, 2024)
Background Music therapy is a rapidly evolving multidisciplinary field. But there has been no research analyzing the latest research status and development trends in this research field from a macro perspective. We aim to identify hotspots, knowledge base, and frontiers in the field of music therapy through bibliometric analysis. Methods All data were retrieved from the Web of Science core database from January 1, 2013 to December 31, 2022.CiteSpace and Bibliometrix software were employed for bibliometric analysis and visualization analysis. Results A total of 2,397 articles were included. In the past decade, there has been a consistent increase in the number of publications. The countries and institutions with the largest production in this field are the USA and the University of London. Based on the analysis of the total number of citations, centrality, and production, the results show that the most influential journals are PLoS One and Cochrane Database Syst Rev. Keyword co-occurrence analysis and highly cited study analysis are mainly used to analyze research hotspots in the field of music therapy, while the keyword burst analysis is employed to explore frontiers and potential developmental trends. Hot keywords include “interventions”, “anxiety” and “randomized controlled trial”. The burst keywords include “validity”, “preterm infants”, and “mild cognitive impairment”. In the ranking of highly cited study, the top ranked studies are “Music-based interventions in neurological rehabilitation” and “Music interventions for improving psychological and physical outcomes in cancer patients”. Conclusion In the past decade, the research focus in music therapy was the effect of music therapy on neurological diseases and the improvement of psychological symptoms such as pain and anxiety. The neurophysiological mechanisms that bring about these therapeutic effects need to be future researched.